A critical review of the development of sustainability indicators for the City of Cape Town : a focus on environmental and socio-economic sustainability - Ndeke, Eunice Ngina (Stellenbosch : Stellenbosch University, 2011)
Thesis (MPhil)--Stellenbosch University, 2011.